Clinical and X-ray Diagnosis of Respiratory Distress in Premature Babies of Less than 34-Week Gestational Age - N. N. Volodin; D. N. Degtyarev; I. Ye Kotik; I. S. Ivanova (Общая реаниматология, 2005)
The study was undertaken to examine the clinical and X-ray features of the respiratory distress syndrome (RDS) in very premature babies. A hundred and thirty-nine cases of respiratory distress were analyzed in premature babies treated at intensive care units. All the infants were born to mothers with a history of gynecological and obstetric diseases in the severe condition. The signs of respiratory distress began to manifest themselves in the babies at a maternity room. Two major clinical and X-ray types of the course of RDS were identified. X-ray studies have established that it is expedient to identify 2 types of the course of RDS in profoundly premature babies in the first 72 hours of life. The first type is characterized by mild or moderate respiratory distress and a favorable course and it corresponds to stages 1—2 according to the X-ray classification. The second type shows a more severe respiratory failure, a greater magnitude of X-ray changes (stages 3—4 by the X-ray classification), and a poor course. A clear distinction of two types of the X-ray pattern of RDS in very premature babies may be of great predictive value.